Influence of ligand substitution at the donor and acceptor center on MMCT in a cyanide-bridged mixed-valence system. Issue 22 (9th May 2019) - Zhang, Lin-Tao; Zhu, Xiao-Quan; Hu, Sheng-Min; Zhang, Yu-Xiao; Su, Shao-Dong; Yang, Yu-Ying; Wu, Xin-Tao; Sheng, Tian-Lu
Abstract : A series of cyanide-bridged complexes [TpmRu(LD )(μ-CN)Ru(LP )Cp*][PF6 ]2 were investigated by changing the substitutions of the donor and acceptor sites to systemically tune MMCT. Abstract : We detail the rational design of bimetallic cyanide-bridged complexes [TpmRu(LD )(μ-CN)Ru(LP )Cp*][PF6 ]2 (Tpm = Tris(1-pyrazolyl)methane, LD = 1, 10-phenanthroline (phen), 2, 2′-bipyridine (bpy), 4, 4′-dimethyl-2, 2′-bipyridine (dbpy), LP = bis(diphenylphosphino)methane (dppm), bis(diphenylphosphino)ethane (dppe), Cp* = 1, 2, 3, 4, 5-pentamethylcyclopentadiene). The metal-to-metal charge transfer (MMCT) properties of these one-electron oxidized complexes were investigated, suggesting that the substitution of the ancillary ligand provides a strong impetus to systematically tune the MMCT properties. The investigation results indicate that all the mixed-valence complexes belong to Class II mixed-valence complexes, according to the Robin-Day classification.